Components of Stress and Their Associations With Sleep Problems: A Cohort Study of Older Employees. Issue 5 (23rd May 2022) - Virtanen, Marianna; Myllyntausta, Saana; Karkkola, Petri; Pentti, Jaana; Ropponen, Annina; Vahtera, Jussi; Stenholm, Sari
Abstract : Clusters of work- and non-work-related stressors were identified and the accumulation of most of these stressors was associated with sleep problems among older employees. This study suggests that measuring both work- and non-work-related stressors as well as their accumulation may be important when assessing the possible etiology of sleep problems among older employees. Abstract : Objective: To identify latent components from among 13 work and nonwork stressors and to examine whether the accumulation of stress factors within these components was associated with sleep problems. Methods: A cohort of older employees (n = 2771 individuals, n = 3921 person-observations) responded to at least two surveys. Principal Component Analysis (PCA) was used to identify latent components. Analysis of variance was used to examine their associations with sleep. Results: The components were: "Physical workload and shift work, " "Psychosocial workload, " "Social and environmental nonwork adversity, " and "Life event- and health-related nonwork adversity." They were consistently associated with sleep problems, except for "Physical workload and shift work." "Social and environmental nonwork adversity" was associated with sleep problems at follow-up. Conclusions: Clusters of work- and nonwork-related stressors were identified, and their accumulation was associated with sleep problems among older employees.